(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Feminists may disagree on the root reasons of women’s subordination, but this is a universalfeature of all dominance hierarchies in interpersonal relationships. Simone de Beauvoir claims that malesplace women in inferior roles because they see women as distinct from themselves (Beauvior 22). Womenare a subservient sex class ruled by patriarchy, as Kate Millet’s theory of subordination demonstrates(Millet 25). Patriarchy is the second major issue that it highlights. In depth exploration accompanied withreference and citation displays to be found in the MLA Handbooks We are making use of the eighthexpansion. All the female protagonists in these works challenge the limiting effects of religion, culture,and society, but they do not follow the same paths as their western counterparts. They like to go theirown separate paths. All of these books have female heroines who are strong and courageous enough tochallenge the constraining effects of religion, society, and culture, but who reject the solutions proposedby their western counterparts. They like to go their own separate paths. The literary representation ofwomen predates the written word. The emergence of women authors, however, has brought aboutdramatic shifts in this depiction. The male-dominated culture that developed these stereotypes portrayedwomen either as vamps or as self-sacrificing angels who would give up all for their loved ones.According to the findings of this research, the depictions of women in works of literature are a crucialcomponent of their overall composition. Also, the depictions of women are the primary means throughwhich the writers in question express their worldviews and societal ideals to their readers. Most of thewriters’ ideas are conveyed via their characters.